The work of difference : modernism, romanticism, and the production of literary form - Wasser, Audrey (Fordham University Press, 2016)
"This book mounts a critique of persistently romantic assumptions in contemporary literary criticism and advances an original theory of literary production. Along the way, it offers new readings of major modernist novels of Samuel Beckett, Marcel Proust, and Gertrude Stein"--